Local Realities and the Adoption of Piecemeal Planning Practices in Mlandizi and Sirari, Tanzania - Yamungu, Nestory E.; Donaldson, Ronnie; Spocter, Manfred (Modern Geográfia, 2025)
Urban planning through local governments is constrained by challenges that place significant burdens on planners. Local realities have a profound influence on planners’ implementation of urban planning policies. This paper draws on the concept of street-level bureaucracy to examine how local realities shape the adoption of piecemeal planning in two small towns in Tanzania. Data were collected through surveys, in-depth interviews, focus group discussions, document reviews, and geospatial analyses of town planning drawings and satellite images. The findings indicate rapid and informal urbanization, evidenced by annual average population growth rates exceeding the national average. Additionally, the proportion of the population living in informal settlements is higher in small towns than in cities. Customary land rights and the informal land market have emerged as the primary drivers of informal settlements. Local governments exhibit low institutional capacity for urban planning, while local politics and market forces further influence the adoption of piecemeal planning practices. The results suggest that these local realities and their interplay create multifaceted complexities, compelling planners to implement urban planning policies in alternative ways. Consequently, piecemeal planning is employed as a strategy to navigate the complexities of urban planning in these two small towns. It is recommended that collaborative efforts between the public and private sectors are essential to integrate structure planning with piecemeal planning, thereby promoting orderly urban development.